The physiotherapy practice for children and adolescents with overweight: A qualitative focus group interview study of physiotherapists' experiences - Malin Vik; Wenche Bjorbækmo; Tone Dahl-Michelsen (Fysioterapeuten, 2023)
Purpose: The purpose of the study is to generate knowledge about the characteristics of the professional physiotherapy practice for children and adolescents with overweight.